Long-term results after the Ross procedure with the decellularized AutoTissue Matrix P® bioprosthesis used for pulmonary valve replacement. (1st December 2018) - Christ, Torsten; Paun, Alexandru Claudiu; Grubitzsch, Herko; Holinski, Sebastian; Falk, Volkmar; Dushe, Simon
Abstract: OBJECTIVES: Since 1967, the Ross procedure has been performed to treat aortic valve disease using homografts for pulmonary valve replacement. The decellularized Matrix P ® prosthesis was developed to overcome (some) limitations of homografts. Until now, the long-term outcome data have been unavailable. METHODS: Between 2002 and 2010, the Ross procedures using the Matrix P prosthesis were performed in 492 adult patients (mean age 57.2 ± 10.6 years, range 21–73 years) at our institution. Patient data were prospectively collected and analysed (3617.3 patient-years, mean follow-up 7.7  ±  4.3 years). Completeness of follow-up at 1, 5 and 10 years was 98.4%, 94.5% and 91.0%, respectively. RESULTS: Hospital mortality was 3.9% ( n   = 19). During follow-up, 121 patients died resulting in a survival rate at 5, 10 and 12.5 years of 82.8  ±  1.7%, 70.4  ±  2.3% and 62.4  ±  2.9%, respectively. Echocardiography revealed a high incidence of relevant dysfunction of the Matrix P prosthesis and subsequent right ventricular failure. Primary reoperation/reintervention was necessary for 150 Matrix P and 48 autografts. Freedom from pulmonary valve reoperation at 5, 10 and 12.5 years was 76.2  ±  2.1%, 58.6  ±  2.9% and 53.4  ±  3.4%, respectively. The autograft function and the left ventricular function showed similar results as previously reported with a freedom from autograft reoperation at 5, 10 and 12.5 years of 91.8  ±  1.4%, 86.1  ±  2.0% and 86.1  ±  2.0%, respectively. CONCLUSIONS: The Matrix P prosthesis used for the right ventricular outflow tract reconstruction in the Ross procedure showed unfavourable long-term echocardiographic results with a high rate of reoperation/reintervention for structural pulmonary valve failure. As a consequence, long-term survival of this patient cohort was impaired. Based on these findings, the use of the Matrix P prosthesis for pulmonary valve replacement for Ross procedures in adults should not be recommended.